A metodologia verbotonal e o desenvolvimento sintático em um paciente com atraso simples de linguagem - Veras, Artemísia Ruth Arruda Lucena (2006)
The aim of this work is to investigate the effects of Verbotonal Methodology on syntactic development of one language simple delayed child. The 5 year old child had been previously chosen for being diagnosticated as showing a language simple delay at the Clínica Escola de Fonoaudiologia da Universidade, João Pessoa - PB, by the Language Pathology Clinic. The work was structured in four steps: first, a semi-structured interview was carried out with the child mother in order to get information about the child neuro-psycho-motor development. Then, the child was submitted to a language pathology test which showed some evidences of telegraphic speech not fitting with her age. After that, the child was submitted to a six month language therapy using the Verbotoal Methodology. By the end of the therapy sessions a language test was again carried out to check the child language syntactic development by using Vilela and Koch (2001) language description model. Aware of the positive results presented by hearing and nonhearing children with the help of Verbotonal Methodology, its use in the case of this child proved to be successful in phonotherapy, with positive results both to the child language improvement and to the work of the language therapist. This paper hopes to give a contribution for the studies on Language therapy as well as to those working with simple delayed language